Exsudação de gel no cozimento em carne de peito de frango normal, PSE e DFD - Praxedes, Carla Inês Soares (2007)
The aiming of this work is to examine the influence of the characteristics of the chicken breast (Pectoralis major) classified as normal, PSE (Pale, Soft, Exudative) and DFD (Dark, Firm, Dry), in the exudation level of gel during the cooking process and co-relate the funcional properties with the respective groups. The number of samples (n=64) of chicken breast (whole-muscle) were visually pre-classified and collected at 90 minutes post mortem, they were boneless and skinless, weighted in half-analytic scale and wrapped in poli nylon bags, kept under refrigeration for 24h at 3.0±2,0°C. After undergone color analysis, registering the values of L* (Luminosity) through system CIE L* a* b* and pH, the results classified the samples in groups: normal, PSE and DFD . The next step was the measurement of the exudates, the water capacity retention, loss of humidity during the cooking process and the gel released during the cooking process. During the drip measurement the results shown that when relating the drip and the pH for the studied groups, where the lowest pH values of 5.67 (±0.07) have shown highest drip values of 5.94 (±0.89) and highest pH values of 6.04 (±0.09) have shown low drip values of 2.26 (±1.63), it was noted a significant difference between the groups for the drip and for the pH, demonstrating that there is influence of the biochemical phenomena. In relation to the water retention capacity amongst the groups, only the DFD had a significant difference, however a significant difference was observed for the group PSE '(r = -0.69 p<0.05) when correlating the water retention capacity and the loss of humidity during the cooking process. In relation to the loss of humidity during the cooking process amongst the groups, only the DFD had a significant difference, however it was noted a significant statistically tendency for the group PSE (r = - 0.59 p<0.05) when correlating the loss of humidity during the cooking process and the pH. During the measurement of the released gel during the cooking process amongst the groups, only the DFD ' had a significant difference, presenting the lowest value (1.13 ±0.44) of released gel during the cooking process. Statistically significant correlations found on the PSE group amongst the values of the water retention capacity and the released gel during the cooking process (r = -0.86 p<0.05) and amongst the values of the loss of humidity during the cooking process and the released gel during the cooking process (r = 0.75 p<0.05). According to the results it can be concluded that the exudates cooking gel has strong influence in the functional properties of the chicken meat PSE and that presents the biggest and negative alterations in relation to the functional properties.